Phase change concrete and preparation method thereof
By performing three-stage surface modification on phase change aggregates to form a three-dimensional encapsulation structure, the problems of phase change material leakage and poor interfacial bonding performance in phase change concrete are solved, achieving high stability and high strength of phase change concrete, which is suitable for large-scale application.
Patent Information
- Application Number
- CN202511493888.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-20
- Publication Date
- 2026-01-13
AI Technical Summary
In the preparation process of existing phase change concrete, the phase change material is prone to leakage and has poor interfacial bonding performance, resulting in reduced compressive strength and durability problems, making it difficult to achieve large-scale application.
By performing three-stage surface modification on phase change aggregates, a three-dimensional encapsulation structure is formed, including an adsorbed paraffin cloud concrete stone, an inner ultra-high performance mortar layer, a foam mortar layer, and an outer ultra-high performance mortar layer, thereby improving interfacial compatibility and stability.
It effectively prevents leakage of phase change materials, improves the overall strength and durability of phase change concrete, and is suitable for large-scale application.
Smart Images

Figure CN121318299A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of concrete, and particularly relates to a phase change concrete and a preparation method thereof. BACKGROUND
[0002] As a new type of green building material, phase change concrete realizes energy storage, energy saving and temperature regulation of building structure through the heat absorption and release characteristics of phase change materials. In recent years, it has attracted widespread attention. Internationally, some progress has been made in the engineering application of phase change concrete in Europe and the United States, such as Germany using phase change concrete to optimize the thermal inertia of building envelope, and the United States using it in solar heat storage systems. In China, the exploration of phase change concrete in the fields of green building and bridge temperature control has been focused on, but the large-scale application is still limited by the problems of material stability and durability.
[0003] At present, the main preparation methods of phase change concrete include direct mixing method, impregnation method and encapsulation method. Among them, the encapsulation method forms "phase change aggregate" by coating phase change materials in porous aggregate (ceramsite, tuff stone, etc.), which can effectively avoid the leakage of phase change materials and improve the cycle stability, and is regarded as the mainstream technical route. However, the interfacial adhesion performance of phase change aggregate and cement matrix directly affects the mechanical properties and durability of concrete. If the surface treatment is not proper, the phase change material is easy to form a weak zone at the aggregate-matrix interface, which leads to the decrease of the compressive strength of concrete (the literature shows that the decrease can be 15%-30%), and even causes the leakage and failure of phase change materials due to the interface cracking.
[0004] In the prior art, the difficulties of surface modification of phase change aggregate are: first, the chemical compatibility of traditional coating materials (such as epoxy resin, silicate) with cement matrix is poor, and it is difficult to form a stable interface; second, the modification process is complex (such as high-temperature sintering or vacuum impregnation), which is high in cost and difficult to be industrialized.
[0005] Therefore, it is urgent to develop a kind of phase change concrete which is efficient, low in cost and highly compatible with cement matrix, and a preparation method thereof. SUMMARY
[0006] The present application proposes a kind of phase change concrete and a preparation method thereof, which solves the problem that phase change material is easy to leak after phase change concrete undergoes phase change cycle through phase change aggregate surface modification method, and also solves the problem of weak interface strength of phase change aggregate-matrix after phase change material leaks, to realize the goal of large-scale application of phase change concrete.
[0007] To solve the above technical problems, the present application includes the following technical solutions:
[0008] A preparation method of a phase change concrete, the preparation method comprising the following steps:
[0009] Step S1, put the cloud stone that needs to be pre-adsorbed with phase change material into an oven, adjust the temperature of the oven to 105±5℃, and bake the cloud stone to constant weight;
[0010] Step S2, put the paraffin phase change material into a container, then put the container containing the paraffin phase change material into an oven at 60℃ for heating, so that the paraffin is in a liquid state; the vacuum kettle is placed in a constant temperature water bath, and the temperature is set to 60℃; put the dried cloud stone into the liquid paraffin, start the vacuum pump, and perform vacuum adsorption; after adsorption, take out the cloud stone, wipe off the residual paraffin on the surface, and weigh after cooling and solidification for standby;
[0011] Step S3, apply ultra-high performance cement mortar to the cloud stone after adsorbing paraffin for the first surface modification to form treated cloud stone;
[0012] Step S4, apply foam mortar to the treated cloud stone for the second surface modification to form foam mortar covered cloud stone;
[0013] Step S5, after the surface mortar of the foam mortar covered cloud stone is initial set and hard, apply ultra-high performance cement mortar to the foam mortar covered cloud stone for the third surface modification;
[0014] Step S6, the cloud stone without adsorbing phase change material is treated by saturated surface dry water absorption;
[0015] Step S7, pour the cloud stone, phase change aggregate, cement, silica fume, and ordinary sand into a concrete mixer for dry mixing for 3.0-5.0 min; pour the high efficiency water reducing agent and water mixed solution into the obtained mixture, and stir for 3.0-5.0 min until the mixture is uniform; add the phase change aggregate three times to the mixture, and stir until the mixture is homogeneous to obtain a new type of high stability phase change concrete.
[0016] Further, the first surface modification method is as follows: place the cloud stone after adsorbing paraffin in a ventilated and dry place to dry, and after the surface is completely hardened, pour it into a concrete measuring cylinder, pour the prepared ultra-high performance cement mortar into the top of the concrete measuring cylinder, slightly stir the cloud stone after adsorbing paraffin until the surface is completely covered with ultra-high performance cement mortar, take out the treated cloud stone, drain the excess mortar, and place it in a ventilated and dry place to dry.
[0017] Further, the proportion of the ultra-high performance cement mortar is as follows: PⅡ52.5 cement 800-1000g; II grade fly ash 40-60g; S95 grade mineral powder 100-120g; 1.6-2.2 fineness modulus fine sand 800-1000g; high efficiency water reducing agent 25-30g; silica fume 40-60g; and water 165-180g.
[0018] Further, the second surface modification method comprises: preparing a foaming agent water solution into foam by a physical method; after the surface mortar of the treated aerated concrete stone is dry and hard after initial setting, pouring into a concrete cylinder, injecting the prepared foam mortar into the concrete cylinder to the top of the concrete cylinder, and stirring slightly until the foam mortar completely covers the surface of the treated aerated concrete stone, and then pouring out; screening the excess foam mortar on the surface of the aerated concrete stone to a thickness of 2-4 mm, and placing in a ventilated and dry place for drying.
[0019] Further, the foam mortar is prepared according to the following proportion:
[0020] PⅡ52.5 cement 230-300 g; II-grade fly ash 20-90 g; fine sand with fineness modulus of 1.6-2.2 500-600 g; foam quality: 20-30 g; water 160-170 g, and the prepared foam mortar has a strength of 0.7-1.5 MPa. The foam is prepared according to the standard "Cast-in-situ Foam Lightweight Soil Technical Specification" (CECS249:2008) by mixing compressed air and a foaming agent water solution.
[0021] Further, the third surface modification method comprises: covering the foam mortar aerated concrete stone, pouring into a concrete cylinder, injecting the prepared ultra-high performance cement mortar into the concrete cylinder to the top of the concrete cylinder, stirring the aerated concrete stone slightly until the surface is completely covered with the ultra-high performance cement mortar, draining the excess mortar on the surface of the aerated concrete stone, and placing in a ventilated and dry place for drying.
[0022] Further, the aerated concrete stone after three surface modifications and adsorption of paraffin wax forms a three-dimensional encapsulation structure, which comprises, from the inside to the outside, the paraffin wax-adsorbed aerated concrete stone, an inner layer of ultra-high performance mortar, a foam mortar layer, and an outer layer of ultra-high performance mortar.
[0023] The application also provides a phase change concrete prepared by the phase change concrete preparation method, and the components of the concrete are as follows in kg / m 3 The components are as follows in mass ratio:
[0024] Aerated concrete stone 450-650; phase change aggregate 200-400; cement 450-550; silica ash 40-60; ordinary sand 600-800; high-efficiency water reducing agent 5-7; and water 120-140.
[0025] Compared with the prior art, the application has the following advantages and beneficial effects:
[0026] This invention provides a phase change concrete and its preparation method. The concrete aggregate, after undergoing three surface modifications and adsorbing paraffin, forms a three-dimensional encapsulated structure. From the inside out, it consists of paraffin-adsorbed concrete aggregate, an inner ultra-high performance mortar layer, a foamed mortar layer, and an outer ultra-high performance mortar layer. The ultra-high performance mortar layer on the inner side of the concrete aggregate acts as the first barrier to prevent the leakage of phase change materials, primarily ensuring that the phase change materials do not leak from the aggregate during daily transportation and concrete preparation. After undergoing multiple phase change cycles, the phase change materials are more prone to leakage from the inner ultra-high performance mortar layer due to factors such as volume changes. With the three-dimensional encapsulation of the phase change aggregate, even if the phase change materials leak from the inner ultra-high performance mortar layer, they will be guided into the loose pores of the foamed mortar and will not directly flow into the concrete substrate mortar, affecting the interfacial strength. The ultra-high performance mortar on the outer side of the encapsulated concrete aggregate is in direct contact with the concrete substrate, improving compatibility with the cementitious matrix, forming a stable interface, and effectively ensuring the overall strength performance of the phase change concrete. Attached Figure Description
[0027] Fig. 1 This is a schematic diagram of step S2 in the preparation method of phase change concrete in one embodiment of the present invention;
[0028] Fig. 2 This is a schematic diagram of foamed mortar in a method for preparing phase change concrete according to an embodiment of the present invention;
[0029] Fig. 3 This is a schematic diagram of a three-dimensional encapsulated structure formed by adsorbing paraffin after three surface modifications in the preparation method of phase change concrete according to an embodiment of the present invention.
[0030] In the picture:
[0031] 1-Phase change paraffin, 2-Vacuum autoclave, 3-Vacuum pump, 4-Container, 5-Mixed concrete, 6-Constant temperature water bath, 7-Adsorbed paraffin mixed concrete, 8-Inner ultra-high performance mortar layer, 9-Foamed mortar layer, 10-Outer ultra-high performance mortar layer. Detailed Implementation
[0032] The present invention provides a phase change concrete and its preparation method, which will be further described in detail below with reference to the accompanying drawings and specific embodiments. The advantages and features of the present invention will become clearer from the following description.
[0033] The following is combined Figs. 1 to 3 This invention provides a detailed description of the phase change concrete and its preparation method.
[0034] A phase change concrete, wherein the components of the concrete are expressed in kg / m³ 3 The mass ratio is:
[0035] Cloud concrete 450-650; phase change aggregate 200-400; cement 450-550; silica fume 40-60; ordinary sand 600-800; high efficiency water reducing agent 5-7; water 120-140.
[0036] The application also provides a preparation method of the phase change concrete, which comprises the following steps:
[0037] Step S1, the cloud concrete 5 needing to be pre-adsorbed with phase change material is placed in an oven, the temperature of the oven is adjusted to 105±5℃, and the cloud concrete is baked to constant weight;
[0038] Step S2, the paraffin phase change material is placed in a container, the container 4 containing the paraffin phase change material is placed in the oven at 60℃ for heating, so that the paraffin is in a liquid state; the vacuum tank 2 is placed in the constant-temperature water bath box 6, and the temperature is set to 60℃; the dried cloud concrete is placed in the liquid paraffin, the vacuum pump 3 is started, and vacuum adsorption is performed; after the adsorption is completed, the cloud concrete is taken out, the residual paraffin on the surface is wiped off, and the cloud concrete is weighed after cooling and solidification for standby use;
[0039] Step S3, the cloud concrete 7 after adsorbing paraffin is subjected to first surface modification by using ultra-high performance cement mortar, and treated cloud concrete is formed; in particular, the first surface modification method is as follows: the cloud concrete 7 after adsorbing paraffin is placed in a ventilated and dry place to dry, after the surface is completely hardened, the treated cloud concrete is poured into a concrete measuring cylinder, the prepared ultra-high performance cement mortar is injected into the concrete measuring cylinder to the top of the cylinder, the cloud concrete after adsorbing paraffin is slightly stirred until the surface is completely covered with the ultra-high performance cement mortar, the treated cloud concrete is taken out, the excess mortar is drained, and the treated cloud concrete is placed in a ventilated and dry place to dry. The ultra-high performance cement mortar is prepared according to the following proportion: PⅡ 52.5 cement 800-1000g; II-grade fly ash 40-60g; S95-grade mineral powder 100-120g; fine sand with a fineness modulus of 1.6-2.2 800-1000g; high efficiency water reducing agent 25-30g; silica fume 40-60g; and water 165-180g.
[0040] Step S4, the treated cloud concrete is subjected to second surface modification by using foam mortar, and foam mortar covered cloud concrete is formed; in particular, the second surface modification method comprises the following steps: a water solution of a foaming agent is prepared into foam by a physical method, specifically, the foaming agent and water are mixed according to a proportion to form a foaming solution, compressed air is introduced, and finally the foam is formed; after the surface mortar of the treated cloud concrete is initially hardened and dry, the treated cloud concrete is poured into a concrete measuring cylinder, the prepared foam mortar is injected into the concrete measuring cylinder to the top of the cylinder, and the treated cloud concrete is slightly stirred until the surface is completely covered with the foam mortar, and then the treated cloud concrete is poured out; the excess foam mortar on the surface of the cloud concrete is screened out to a thickness of 2-4mm, and the foam mortar covered cloud concrete is placed in a ventilated and dry place to dry for standby use.
[0041] The foam mortar is prepared according to the following proportion:
[0042] The foamed mortar prepared using the following methods has a strength of 0.7–1.5 MPa: 230–300 g of PⅡ52.5 cement; 20–90 g of Grade II fly ash; 500–600 g of fine sand with a fineness modulus of 1.6–2.2; 20–30 g of foam; and 160–170 g of water. The foam is produced according to the standard "Technical Specification for Cast-in-Place Foamed Lightweight Soil" (CECS249:2008), using a mixture of compressed air and a foaming agent aqueous solution.
[0043] Step S5: After the surface mortar of the foamed mortar-covered cloud concrete stone has initially set and hardened, apply ultra-high performance cement mortar to the foamed mortar-covered cloud concrete stone for a third surface modification. The third surface modification method includes: pouring the foamed mortar-covered cloud concrete stone into a concrete measuring cylinder, injecting the mixed ultra-high performance cement mortar into the concrete measuring cylinder until it reaches the top of the measuring cylinder, gently stirring the cloud concrete stone until the surface is completely covered with ultra-high performance cement mortar, draining off the excess mortar from the surface of the cloud concrete stone, and placing it in a ventilated and dry place to dry.
[0044] Step S6: Perform saturated surface dry water absorption treatment on the unadsorbed phase change material cloud concrete stone;
[0045] Step S7: Pour the concrete aggregate, phase change aggregate, cement, silica fume, and ordinary sand into a concrete mixer and dry mix for 3.0 to 5.0 minutes. Add the high-efficiency water-reducing agent and water mixture to the mixture and stir for 3.0 to 5.0 minutes until the mixture is uniform. Add the triple-encapsulated phase change aggregate to the mixture and stir until it reaches a homogeneous state to obtain a new type of high-stability phase change concrete.
[0046] Specifically, the cloud concrete stone after three surface modifications and paraffin adsorption forms a three-dimensional encapsulation structure, consisting of paraffin adsorption cloud concrete stone 71, inner ultra-high performance mortar layer 8, foam mortar layer 9, and outer ultra-high performance mortar layer 10, from the inside out.
[0047] The following are specific embodiments; the phase change concrete mix proportion table is shown in Table 1.
[0048] Example:
[0049] Table 1. Mix Proportioning Table for Phase Change Concrete
[0050]
[0051] Phase change concrete phase change cycle strength test:
[0052] The phase change concrete mixed with different proportions and different types of phase change aggregate at the age of 28d is put into a constant temperature and humidity box with a set temperature of 10℃ for 120min, so that the phase change aggregate in the concrete is fully cooled to solid state; then it is put into a constant temperature and humidity box with a set temperature of 60℃ for 120min, so that the phase change aggregate in the concrete is stored heat to liquid state, which is a phase change cycle.
[0053] The mechanical properties of the phase change concrete are tested according to the standard GB / T 50081-2019 'Standard Test Methods for Physical and Mechanical Properties of Concrete'.
[0054] Table 2: Performance table of phase change concrete
[0055]
[0056] It can be known from the comparison of examples 1 to 4 that the compressive strength of the phase change concrete prepared by the method of the application is generally better than that of ordinary phase change concrete after multiple phase change cycles, which improves the stability and durability of the material.
[0057] The above examples are the preferred embodiments of the present application, but the embodiments of the present application are not limited by the above examples. The above examples only express several embodiments of the present application, and the description is more specific and detailed, but it cannot be understood as limiting the scope of the patent. It should be pointed out that for ordinary skilled in the art, without departing from the concept of the present application, some modifications and improvements can be made, which are all within the protection scope of the present application. Therefore, the protection scope of the patent of the present application should be subject to the appended claims.
Claims
1. A method for preparing phase change concrete, characterized in that, Includes the following steps: Step S1: Place the concrete stone that needs to be pre-adsorbed with phase change material into an oven, and adjust the oven temperature to 105±5℃ to dry the concrete stone to constant weight. Step S2: Place the paraffin phase change material into a container, and then place the container containing the paraffin phase change material into an oven at 60°C for heating, so that the paraffin is in a liquid state; place the vacuum vessel in a constant temperature water bath and set the temperature to 60°C; put the dried concrete stone into the liquid paraffin, turn on the vacuum pump, and perform vacuum adsorption; after the adsorption is completed, take out the concrete stone, wipe off the residual paraffin on the surface, and weigh it after cooling and solidification for later use. Step S3: Apply ultra-high performance cement mortar to perform the first surface modification on the paraffin-adsorbed cloud concrete stone to form the treated cloud concrete stone. Step S4: Apply foamed mortar to the treated cloud concrete stone for a second surface modification to form a cloud concrete stone covered with foamed mortar. Step S5: After the mortar covering the foamed mortar cloud concrete stone has initially set and hardened, apply ultra-high performance cement mortar to the foamed mortar cloud concrete stone for a third surface modification. Step S6: Perform saturated surface dry water absorption treatment on the unadsorbed phase change material cloud concrete stone; Step S7: Pour the concrete aggregate, phase change aggregate, cement, silica fume, and ordinary sand into a concrete mixer and dry mix for 3.0 to 5.0 minutes. Add the high-efficiency water-reducing agent and water mixture to the mixture and stir for 3.0 to 5.0 minutes until the mixture is uniform. Add the triple-encapsulated phase change aggregate to the mixture and stir until it reaches a homogeneous state to obtain a new type of high-stability phase change concrete.
2. The preparation method according to claim 1, characterized in that, The first surface modification method is as follows: After the paraffin-adsorbed concrete stone is placed in a ventilated and dry place to dry, it is poured into a concrete measuring cylinder after the surface is completely hardened. The mixed ultra-high performance cement mortar is then poured into the concrete measuring cylinder until it reaches the top of the measuring cylinder. The paraffin-adsorbed concrete stone is stirred slightly until the surface is completely covered with ultra-high performance cement mortar. The treated concrete stone is then removed, excess mortar is drained off, and it is placed in a ventilated and dry place to dry.
3. The preparation method according to claim 2, characterized in that, The ultra-high performance cement mortar mix proportions are as follows: 800-1000g of PⅡ52.5 cement; 40-60g of Grade II fly ash; 100-120g of S95 grade mineral powder; 800-1000g of fine sand with a fineness modulus of 1.6-2.2; 25-30g of high-efficiency water-reducing agent; 40-60g of silica fume; 165-180g of water.
4. The preparation method according to claim 1, characterized in that, The second surface modification method includes: preparing foam from a foaming agent aqueous solution using physical methods; after the mortar on the surface of the treated concrete stone has initially set and hardened, pouring it into a concrete measuring cylinder, injecting the mixed foamed mortar into the concrete measuring cylinder until it reaches the top of the measuring cylinder, stirring slightly until the surface of the treated concrete stone is completely covered with foamed mortar, and then pouring it out; sieving out excess foamed mortar from the surface of the concrete stone until the mortar thickness is 2-4 mm, and placing it in a ventilated and dry place to dry for later use.
5. The preparation method according to claim 4, characterized in that, The foamed mortar mix proportions are as follows: 230-300g of PⅡ52.5 cement; 20-90g of Grade II fly ash; 500-600g of fine sand with a fineness modulus of 1.6-2.2; 20-30g of foam. Using 160-170g of water, the strength of the prepared foam mortar is 0.7-1.5MPa.
6. The preparation method according to claim 4, characterized in that, The third surface modification method includes: pouring foamed mortar-covered marble into a concrete measuring cylinder, injecting mixed ultra-high performance cement mortar into the concrete measuring cylinder until it reaches the top of the measuring cylinder, lightly stirring the marble until the surface is completely covered with ultra-high performance cement mortar, draining excess mortar from the surface of the marble, and placing it in a ventilated and dry place to dry.
7. The preparation method according to claim 6, characterized in that, After undergoing three surface modifications, the paraffin-adsorbed marble forms a three-dimensional encapsulated structure, consisting of paraffin-adsorbed marble, an inner ultra-high performance mortar layer, a foam mortar layer, and an outer ultra-high performance mortar layer, from the inside out.
8. A phase change concrete, characterized in that, The concrete is prepared using the phase change concrete preparation method according to any one of claims 1 to 7, wherein the components of the concrete are measured in kg / m³. 3 The mass ratio is: Cloud concrete aggregate 450-650; phase change aggregate 200-400; cement 450-550; silica fume 40-60; Ordinary sand 600-800; high-efficiency water-reducing agent 5-7; water 120-140.
Citation Information
Cited By
Sophorolipid modified recycled aggregate, phase change concrete and preparation method thereof
CN122079521A